The effect of temperature shifts on N2O and NO emissions from a partial nitritation reactor treating reject wastewater. (December 2018) - Bao, Zhiyuan; Ribera-Guardia, Anna; Spinelli, Matteo; Sun, Dezhi; Pijuan, Maite
Abstract: Temperature has a known effect on ammonia oxidizing bacteria (AOB) activities, reducing its ammonia oxidizing rate (AOR) when temperature is lowered. However, little is known concerning its effect on N2 O and NO emissions which are produced during ammonia oxidation having a greenhouse effect. To study this, an AOB enriched partial nitrification sequencing batch reactor (PN-SBR) was operated within a two step-wise feed under 5 different temperatures (30-25-20-15-10 °C). A decrease on the specific AOR ( s AOR) was detected when decreasing the temperature. N2 O emissions were also affected by the temperature but only the ones produced during the first aeration of the cycle, when AOBs shifted from a period of low activity to a period of high activity. N2 O emission factors (%) detected during the second aerobic phase were similar among all temperatures tested and lower than the emissions detected during the first aerated phase. The average N2 O emission factor was in the range of 0.15–0.70% N2 O-N/NH4 + -N oxidized in the first aeration phase and 0.14–0.15% N2 O-N/NH4 + -N-oxidized in the second aeration phase at 10 to 30 °C, respectively. On the other hand, NO emissions were very similar under all temperatures resulting in 0.03–0.06% of NH4 + -N oxidized. Graphical abstract: Highlights: N2 O and NO were measured in PN-SBR in the range of 30–10 °C. N2 O peak emissions were related to the transition from low to high activity. N2 O emissions were affected by temperature in the first aeration. NO emissions were not affected by temperature.